Distance Measurement using an Infrared Distance Sensor Based on Lagrange and Newton Interpolating Polynomials. - Abdullah, Rawaz H. (Sulaimani Journal for Pure and Applied Sciences, 2015)
This paper presents two models for distance measurement to a very popular infrared (IR) distance measuring sensor from SHARP, which has applications in projects that require cheap and accurate distance measurements. The sensor outputs a voltage at any distance (with a range from 10 cm to 80 cm) from an object based on the optical triangulation method. The variety of the reflectivity of the object, the environmental temperature and the operating duration are not influenced easily to the distance detection. The presented models in this paper are based on Newton and Lagrange interpolating polynomials, which require a few data points to compute the polynomial equations and thereby the distance from any object could be computed easily. The expected errors in distance estimation for the two proposed models are analyzed. As it is evident from the results, the two models could be used easily with insignificant amount of error.
Keywords: Infrared IR distance measuring sensor; distance measurement; optical triangulation method; Newton and Lagrange interpolating polynomials; error estimation